(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
It is generally accepted that Arabic has had a major impact on the growth of the Swahili language over the centuries. The meaning of this linguistic stimulus of Arabic, however, has been a matter of far lesser consensus in both the colonial and postcolonial dispensations. Does the Semitic influence reduce Swahili’s African credentials, and does it amount to some degree of linguistic Islamization? If so, is the development an argument in favor of or against Swahili in relation to its role as a language of Christianity and, later of national belonging and expression? And can one be anti-Arab and anti- Islam but pro-Swahili at the same time without having to dis-Arabize Swahili? These are some of the central questions addressed in this article, reflecting conflicting positions of various interest groups, even as Swahili’s own momentum and dynamism have increasingly neutralized the contestation over its identity.